Field evaluation of tractor-operated seeder for sowing mat type paddy nursery - MODI, RAJESH U; MANES, G S; MAHAL, J S; DIXIT, A K; SINGH, ARSHDEEP; MAHAL, A K (The Indian Journal of Agricultural Sciences, 2022)
Mat-type nursery having uniform growth is a prerequisite for mechanized paddy transplanting. Generally, this type of nursery is sown manually in the open field or in trays. It requires several simultaneous operations and hence is laborious and time-consuming. The performance of tractor-operated mat-type nursery seeder was evaluated at the Research Farm of Punjab Agricultural University, Ludhiana, Punjab during 2019–20 with an objective to obtain the finest speed of operation to get the uniform seed and soil spread. Study was carried out on three different types of soil (sandy loam, loam and silt loam) for three different forward speeds (1.7, 2.2 and 2.7 km/h). Results have shown that the soil type had a non-significant effect on the performance of the machine, whereas forward speed had significant (P<0.05) effect. In overall, with an increase in forward speed of the machine, there was a reduction in uniformity for both seed and soil spread. The best results were obtained at a forward speed of 1.7 km/h with the overall seed spread of 90.93%, overall soil mat thickness 99.70%, fuel consumption 4.36 l/h and effective field capacity 0.092 ha/h. Therefore, the developed tractor-operated seeder can be operated on sandy loam to silt loam soils with a forward speed of 1.7 km/h with 59.5% saving in cost and 62.6% saving in labour for sowing mat type nursery as compared to manual method with MS frames.